Subjectivity, Multiple Drafts and the Inconceivability of Zombies and the Inverted Spectrum in this World. - Schier, Elizabeth (Topoi: An International Review of Philosophy, 2019)
Proponents of the hard problem of consciousness argue that the zombie and inverted spectrum thought experiments demonstrate that consciousness cannot be physical. They present scenarios designed to demonstrate that it is conceivable that a physical replica of someone can have radically different or no conscious experiences, that such an experience-less replica is possible and therefore that materialism is false. I will argue that once one understands the limitations that the physics of this world puts on cognitive systems, zombies and the inverted spectrum are not conceivable.